2020
DOI: 10.1088/1757-899x/736/2/022021
|View full text |Cite
|
Sign up to set email alerts
|

Growth and yield of Pleurotus ostreatus using sugarcane bagasse as an alternative substrate in Malaysia

Abstract: This paper looks at the feasibility of using sugarcane bagasse (SGB) for the cultivation of Pleurotus ostreatus (oyster mushrooms) as an alternative for rubber tree sawdust (RS). Three different compositions of oil palm trunk and rubber tree sawdust were studied with each composition having three replicates. A substrate containing only rubber tree sawdust acted as the control variable. The substrates were supplemented with 5% rice bran and 1.5% calcium carbonate. There are four steps involved in the cultivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The fertility parameter of individual strains may be significant, as there is evidence that the biological efficiency of individual strains may vary [ 62 , 63 , 64 ]. Pleurotus ostreatus species is quite unique because they are able to grow on different agrowaste materials [ 65 ], such as rice straw [ 66 ], oil palm fronds [ 67 ], empty fruit bunch and palm-pressed fiber [ 68 ], sugarcane bagasse [ 69 ], corn cob [ 70 ] wheat straw, coffee waste, and leaf litter of forest trees [ 71 ]. If the strain is characterized by a high content of β-glucans but is low in crop, it is not an important source of biologically valuable substances for the producer.…”
Section: Resultsmentioning
confidence: 99%
“…The fertility parameter of individual strains may be significant, as there is evidence that the biological efficiency of individual strains may vary [ 62 , 63 , 64 ]. Pleurotus ostreatus species is quite unique because they are able to grow on different agrowaste materials [ 65 ], such as rice straw [ 66 ], oil palm fronds [ 67 ], empty fruit bunch and palm-pressed fiber [ 68 ], sugarcane bagasse [ 69 ], corn cob [ 70 ] wheat straw, coffee waste, and leaf litter of forest trees [ 71 ]. If the strain is characterized by a high content of β-glucans but is low in crop, it is not an important source of biologically valuable substances for the producer.…”
Section: Resultsmentioning
confidence: 99%
“…5,21,22 Various studies suggested that sugarcane bagasse is a good source for the cultivation of P. ostreastus. 23,24 Their studies showed that biomass from sugarcane either used alone, or in combination with other substrates, such as rubber tree sawdust and wheat straw, can increase the yield of oyster mushrooms. In this study, P. ostreatus PO3 also grew well on sugarcane bagasse; however, P. pulmonarius PP6 hardly grew on the same substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, an 80% hardwood sawdust and 20% additive mixture is used as the standard substrate formula for shiitake cultivation [ 23 ]. However, this study used a starch-based substrate (sugarcane bagasse) as the main substrate as used by [ 24 , 25 ] and supplemented it with nutrient additives such as cow dung, horse manure, chicken manure, or sugarcane filter cake, which we assumed would enhance mushroom yields due to their high nutrient content [ 26 ]. Mushrooms can grow and provide higher yields when using a substrate of optimal C:N [ 27 ].…”
Section: Introductionmentioning
confidence: 99%